Transition impossible? Ukraine between violence and power. Issue 3 (2nd September 2017) - Oleinik, Anton
Abstract: This article discusses authority culture in Ukraine. 'Russian power', i.e. a particular configuration of power relationship that has been prevailing in the Russian, Soviet and post-Soviet empires, is used as a point of reference. Two features of Russian power explain its closeness to violence: mostly negative associations (such as force, money and corruption) and a high power distance. It is argued that a potential movement from violence to power understood as human ability to act in concert exists in Ukraine. Members of Ukraine's sub-elites have a chance to become a driving force of this process. Under certain conditions they could take a lead in transitioning to less violent models of power in politics and elsewhere. The data were drawn from three mass surveys conducted in Russia ( N = 2939 and N = 11, 096) and in Ukraine ( N = 2040) from July 2016 to January 2017.